2016
DOI: 10.1128/jvi.00411-16
|View full text |Cite
|
Sign up to set email alerts
|

The Human Papillomavirus 16 E7 Oncoprotein Attenuates AKT Signaling To Promote Internal Ribosome Entry Site-Dependent Translation and Expression of c-MYC

Abstract: While the role of high-risk human papillomavirus (HPV) oncoproteins E6 and E7 in targeting p53 and retinoblastoma (Rb) has been intensively studied, how E6 and E7 manipulate cellular signaling cascades to promote the viral life cycle and cancer development is less understood. Keratinocytes containing the episomal HPV-16 genome had decreased activation of AKT, which was phenocopied by HPV-16 E7 expression alone. Attenuation of phosphorylated AKT (pAKT) by E7 was independent of the Rb degradation function of E7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…NIKS were retrovirally transduced with replication defective murine retroviruses or transfected with the HPV-16 genome as previously described (Lambert et al, 2005). To investigate YAP localization on coverslips, NIKS cells were treated by cell starvation and stimulation assays as described (Strickland and Vande Pol, 2016). Briefly, 4x10 5 trypsinized NIKS cells were plated on glass coverslips in 6-well plates (Day 1) together with mitomycin C treated feeder cells.…”
Section: Methodsmentioning
confidence: 99%
“…NIKS were retrovirally transduced with replication defective murine retroviruses or transfected with the HPV-16 genome as previously described (Lambert et al, 2005). To investigate YAP localization on coverslips, NIKS cells were treated by cell starvation and stimulation assays as described (Strickland and Vande Pol, 2016). Briefly, 4x10 5 trypsinized NIKS cells were plated on glass coverslips in 6-well plates (Day 1) together with mitomycin C treated feeder cells.…”
Section: Methodsmentioning
confidence: 99%
“… 10 PI3K could be activated by many types of cellular stimuli, which subsequently phosphorylates the inositol PIP2 to PIP3 that recruits Akt to the plasma membrane by binding to its N-terminal pleckstrin homology (PH) domain in which Akt gets activation via phosphorylation. 11 As a serine/threonine kinase, phosphorylated Akt is able to stimulate mTOR which belongs to a member of the serine/threonine phosphatidyl inositol 3′ kinase-related kinase family (PIKK). 10 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that HPV E6 and E7 oncogenes augment the activation of AKT [ 32 , 34 ]. Nonetheless, a recent study showed that HPV-16 E7 can attenuate pAKT signalling [ 35 ]. In addition, hypoxic AKT activation is observed under conditions of E6/E7 repression [ 36 ], which indicates that the hypoxic AKT activation is regulated by an E6/E7-independent mechanism, but the mechanism is unclear.…”
Section: Discussionmentioning
confidence: 99%